BRIEFING NOTE ABOUT ACTIVITY OF EDITORIAL BOARD OF "RATIONAL PHARMACOTHERAPY IN CARDIOLOGY" IN 2009 (Столичная издательская компания, 2016)
Briefing note about activity of editorial board of "Rational Pharmacotherapy in Cardiology" in 2009.